ZooZical - Sierra, Judy; Brown, Marc Tolon (New York : Alfred A. Knopf, 2011)
When the winter doldrums arrive at the zoo, a very small hippo and a young kangaroo decide to stage a "ZooZical," a show to display their singing, dancing, acrobatic, and other talents to the people of Springfield.
Keywords: Talent shows -- Fiction; Zoo animals -- Fiction; Animals -- Fiction; Stories in rhyme